Temporal-order discrimination for selected auditory and visual stimulus dimensions. - McFarland DJ; Cacace AT; Setzen G (Journal of Speech, Language & Hearing Research, 1998)
Thresholds for the discrimination of temporal order were determined for selected auditory and visual stimulus dimensions in 10 normal-adult volunteers. Auditory stimuli consisted of binary pure tones varying in frequency or sound pressure level, and visual stimuli consisted of binary geometric forms varying in size, orientation, or color. We determined the effect of psychophysical method and the reliability of performance across stimulus dimensions. Using a single-track adaptive procedure, Experiment 1 showed that temporal-order thresholds (TOTs) varied with stimulus dimension, being lowest for auditory frequency, intermediate for size, orientation, and auditory level, and longest for color. Test performance improved over sessions and the profile of thresholds across stimulus dimensions had a modest reliability. Experiment 2 used a double-interleaved adaptive procedure and TOTs were similarly ordered as in Experiment 1. However, TOTs were significantly lower for initially ascending versus descending tracks. With this method, the reliability of the profile across stimulus dimensions and tracks was relatively low. In Experiment 3, psychometric functions were obtained for each of the stimulus dimensions and thresholds were defined as the interpolated 70.7% correct point. The relative ordering of TOTs was similar to those obtained in the first two experiments. Non-monotonicities were found in some of the psychometric functions, with the most prominent being for the color dimension. A cross-experiment comparison of results demonstrates that TOTs and their reliability are significantly influenced by the psychophysical method. Taken together, these results support the notion that the temporal resolution of ordered stimuli involves perceptual mechanisms specific to a given sensory modality or submodality.